2015
DOI: 10.5194/acp-15-3277-2015
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscale modelling study of the interactions between aerosols and PBL meteorology during a haze episode in China Jing–Jin–Ji and its near surrounding region – Part 2: Aerosols' radiative feedback effects

Abstract: Abstract.Two model experiments, namely a control (CTL) experiment without aerosol-radiation feedbacks and a experiment with online aerosol-radiation (RAD) interactions, were designed to study the radiative feedback on regional radiation budgets, planetary boundary layer (PBL) meteorology and haze formation due to aerosols during haze episodes over Jing-Jin-Ji, China, and its near surroundings (3JNS region of China: Beijing, Tianjin, Hebei, East Shanxi, West Shandong and North Henan) with a two-way atmospheric … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
63
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(73 citation statements)
references
References 31 publications
10
63
0
Order By: Relevance
“…For the diurnal cycle, the increase of surface PM 2.5 concentration is more predominant at around 10:00-18:00 LT, with an average value ranging from 10 to 15 μg m −3 (12-16%). Wang et al (2015) also indicated that the more stable atmospheric stratification from diurnal timing (Fig. 6f) and areas ( Fig.…”
Section: Radiation Feedback On Aerosol and Ozone Photochemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…For the diurnal cycle, the increase of surface PM 2.5 concentration is more predominant at around 10:00-18:00 LT, with an average value ranging from 10 to 15 μg m −3 (12-16%). Wang et al (2015) also indicated that the more stable atmospheric stratification from diurnal timing (Fig. 6f) and areas ( Fig.…”
Section: Radiation Feedback On Aerosol and Ozone Photochemistrymentioning
confidence: 99%
“…6e). Wang et al (2015) designed similar experiments and found that atmospheric aerosols cooled the PBL but warmed the atmosphere above it in northern China, leading to a more stable atmospheric stratification and a decrease in PBL height by about 33%.…”
Section: Ozone Photochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between key PBL meteorological factors, PM 2.5 and the haze episode is analyzed. The impact of aerosols on local PBL is presented in a companion paper (Part 2, Wang et al, 2015).…”
Section: H Wang Et Al: Study Of the Interactions Between Aerosols Amentioning
confidence: 99%
“…A more detailed description of CUACE can be found in Gong and Zhang (2008). And it has been evaluated and applied systematically in previous studies Wang et al, 2015b;He et al, 2016b). The FLEXPART model, developed by the Norwegian Institute of Air Research, is a Lagrangian transport and dispersion model that is suitable for the simulation of atmospheric transport processes.…”
Section: Methodsmentioning
confidence: 99%